Bio‐Inspired Hierarchical Chiral Metamaterials: Near‐Field Coupling and Decoupling Effects Modulating Microwave‐Stealth Properties. Issue 20 (17th July 2022) - Shi, Yupeng; Duan, Yuping; Huang, Lingxi; Pang, Huifang; Ma, Xinran; Liu, Xiaoji; Li, Zerui
Abstract: Polarization conversion of chiral ordered structures can achieve effective electromagnetic attenuation through flexible field rotation. However, the mechanism of near‐field coupling generation on which it depends remains unclear, hindering the development of chiral wave‐absorbing materials. In this work, a beetle‐inspired ordered structure, which is a kind of chiral metamaterials (CMMs) consisting of high entropy alloy (HEA) electromagnetic dissipative unit and media‐layer, is rationally designed. Such CMMs show that the coupling and decoupling effects can achieve dynamic conversion between linearly polarized waves and circularly polarized waves, and the mechanisms analyzed and verified by simulation models confirm that as a universal method. The fabricated biomimetic metamaterials show desirable absorption with effective absorption bandwidth of 4.48 GHz at 2 mm interlayer medium thickness (≥75% absorptivity, reflection loss ≤ −6 dB) and minimum reflection loss (RLmin ) of −53.6 dB. Moreover, pasting the flexible CMMs conformally on conventional coating surfaces can boost microwave‐invisible capacity, whose absorption bandwidth with RL lower than −6 dB increases to 5.18 GHz over HEA coating. In short, this work elucidates the mechanism of chiral near‐field coupling and provides a novel solution principle and methodology for using CMMs in wave‐absorbing materials. Abstract : In order to elucidate the generation mechanism of chiral near‐field coupling effect, a new hierarchical chiral wave‐absorbing metamaterial is proposed with the bionic concept. The rational modulation of the coupling effect induces the dynamic transformation from linearly polarized waves to circularly polarized waves, providing a new idea and method for designing chiral stealth metamaterials.